2013
DOI: 10.1186/1748-717x-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal avoidance with volumetric modulated arc therapy in melanoma brain metastases – the first Australian experience

Abstract: PurposeVolumetric modulated arc therapy (VMAT) can deliver intensity modulated radiotherapy (IMRT) like dose distributions in a short time; this allows the expansion of IMRT treatments to palliative situations like brain metastases (BMs). VMAT can deliver whole brain radiotherapy (WBRT) with hippocampal avoidance and a simultaneous integrated boost (SIB) to achieve stereotactic radiotherapy (SRT) for BMs. This study is an audit of our experience in the treatment of brain metastases with VMAT in our institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…Both planning techniques were able to achieve adequate whole‐brain coverage and radiosurgical quality of dose distributions to each of the brain metastases and spared hippocampi. A study by Awad et al (26) presented clinical data on hippocampus sparing for WBRT patients using VMAT with SIB for brain metastases from primarily melanoma origin. In their institution, 30 patients with 73 brain tumors were treated with VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…Both planning techniques were able to achieve adequate whole‐brain coverage and radiosurgical quality of dose distributions to each of the brain metastases and spared hippocampi. A study by Awad et al (26) presented clinical data on hippocampus sparing for WBRT patients using VMAT with SIB for brain metastases from primarily melanoma origin. In their institution, 30 patients with 73 brain tumors were treated with VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…The dose to the region of the hippocampus may delay or reduce neurocognitive deterioration [16,18], giving higher doses to the macroscopic metastases should progression of intracranial disease. We think this goal is achievable adopting Tomo-Therapy with WBRT-HS/SIB (our proposed schedule).We started a Phase II randomized trial of comparison between WBRT and WBRT-HS/SIB in oligometastatic patients to elucidate the real benefit of the new technique in this setting.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has therefore prompted several researchers to investigate the selective avoidance of certain brain areas. The impairment of learning, memory, and motor coordination seem to be linked to irradiation of the hippocampus [16][17][18][19][20]. Despite the fact that these functions are located in different brain areas, the pathogenetic hypothesis of these changes can be attributed to radiation damage suffered by the progenitor cells that are in the sub-granular zone of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Many planning studies have shown the dosimetric feasibility of hippocampus avoiding (HA) WBRT in different clinical situations using many different radiotherapy systems and techniques [2][3][4][5] . However, these studies must be considered as experimental until well designed clinical trials with appropriate endpoints definitely reveal the significant clinical benefit of these novel approaches 2,6 .…”
Section: Introductionmentioning
confidence: 99%